(3HZjI GdWGdHjf hQZHI GdQGZHjfs - (3eMeO Hf YeQ Hf bGSe Hf ESeGYjd GdHbQj,J (B1111 (3g` s
(3ChdgG (B:s
(3hHYO agPG HZjI GdWGdHjf hQZHI GdQGZHjf GdHGH GdChd aj GdfMh hajg aUhd aUd ai eNGQL GdMQha hUaGJgG s
(3BNQgG (B:s
(3hbjd GdfGS hdjS ajgG CjVkG hba MSf eYJeO hGddg GYde s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B317 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B89s
(3eUOQ GbJfGA GdCUd (B:s
(3GdecJHI GdCRgQjI (B((3bQGAGJ (B193) s
Keywords: (3GdbQGAGJ hGdJLhjOs